Exploring Tourist Satisfaction: A Study of Domestic Visitors at Shivapuri Nagarjun National Park - Sharma, Laxmi Kanta (Journal of Development and Administrative Studies, 2018)
This study presents a comprehensive analysis of the tourist satisfaction and market competition environment of Shivapuri National Park as a tourist destination. The study defines the relevant concepts related to tourist destinations and satisfaction and conducts a SWOT analysis to evaluate the internal and external factors affecting the park. To gather empirical data, an email questionnaire survey was conducted, and responses from 210 domestic tourists were collected to investigate the actual conditions of the park and satisfaction levels based on 18 indicators. The research identifies practical issues that hinder the improvement of tourist satisfaction and proposes measures to enhance the overall experience of tourists. The findings of the study provide valuable insights into park management, which can be used to develop effective strategies for attracting more tourists and improving their overall satisfaction levels. The research highlights the importance of understanding the tourist satisfaction and market competition environment of national parks and the need for regular monitoring and evaluation to ensure sustainable tourism development.